Pharmacological Neuroprotection of the Preterm Brain: Current Evidence and Perspectives - Siahanidou, Tania; Spiliopoulou, Christina (American Journal of Perinatology, 2020)
Despite improvements in viability, the long-term neurodevelopmental outcomes of preterm babies remain serious concern as a significant percentage of these infants develop neurological and/or intellectual impairment, and they are also at increased risk of psychiatric illnesses later in life. The current challenge is to develop neuroprotective approaches to improve adverse outcomes in preterm survivors. The purpose of this review was to provide an overview of the current evidence on pharmacological agents targeting the neuroprotection of the preterm brain. Among them, magnesium sulfate, given antenatally to pregnant women with imminent preterm birth before 30 to 34 weeks of gestation, as well as caffeine administered to preterm infants after birth, exhibited neuroprotective effects for human preterm brain. Erythropoietin treatment of preterm infants did not result in neuroprotection at 2 years of age in two out of three published large randomized controlled trials; however, long-term follow-up of these infants is needed to come to definite conclusions. Further studies are also required to assess whether melatonin, neurosteroids, inhaled nitric oxide, allopurinol, or dietary supplements (omega-3 fatty acids, choline, curcumin, etc.) could be implemented as neuroprotectants in clinical practice. Furthermore, other pharmacological agents showing promising signs of neuroprotective efficacy in preclinical studies (growth factors, hyaluronidase inhibitors or treatment, antidiabetic drugs, cannabidiol, histamine-H3 receptor antagonists, etc.), as well as stem cell- or exosomal-based therapies and nanomedicine, may prove useful in the future as potential neuroprotective approaches for human preterm brain.Key Points
Keywords: brain; prematurity; neonates; drugs; neuroprotective agents; medications